GE_GERICHTE A/2336/2024 vom 6. November 2024 - GE Cour de justice (2024)
RETRAIT DE PERMIS;PÉRIODE D'ESSAI;PERMIS DE CONDUIRE | LCR.15a; OAC.35.al1; LCR.15b; LCR.16a.al1.leta; LCR.16.al2; LCR.16c.al2.leta; LCR.16.al3